2013
DOI: 10.1071/sh13034
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and understanding barriers to sexually transmissible infection testing among young people

Abstract: (2013) Identifying and understanding barriers to sexually transmissible infection testing among young people. Sexual Health, 10. pp. 553-558. ISSN 1448-5028 This version is available from Sussex Research Online: http://sro.sussex.ac.uk/49734/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
3
27
2
1
Order By: Relevance
“…This finding is higher than the previous study done in Machakle district [ 13 ] and this difference might be due to difference in time and/or to sociocultural variations. However, this finding was much lower than studies done in Harar [ 8 ], Botswana [ 16 ] and England [ 17 ]. This might be due to differences in the availability or accessibility of Youth Friendly Health facilities or Youth Centers, educational status/level, socio-economic status, urban-rural residence, transportation and cultural variations.…”
Section: Discussioncontrasting
confidence: 69%
“…This finding is higher than the previous study done in Machakle district [ 13 ] and this difference might be due to difference in time and/or to sociocultural variations. However, this finding was much lower than studies done in Harar [ 8 ], Botswana [ 16 ] and England [ 17 ]. This might be due to differences in the availability or accessibility of Youth Friendly Health facilities or Youth Centers, educational status/level, socio-economic status, urban-rural residence, transportation and cultural variations.…”
Section: Discussioncontrasting
confidence: 69%
“…Most participants did not feel they were at risk of contracting STIs and, even after deciding to have an STI test, very few believed they would receive a positive STI test result. This lack of risk perception has been reported in other studies 23–27 . Participants generally felt that they could judge for themselves whether a sexual partner or potential partner was ‘clean’ or not.…”
Section: Discussionsupporting
confidence: 62%
“…This lack of risk perception has been reported in other studies. [23][24][25][26][27] Participants generally felt that they could judge for themselves whether a sexual partner or potential partner was 'clean' or not. Participants would look for indicators of 'dirtiness' , including the way individuals dressed and acted.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional STI research has shown that STI testing rates can vary substantially according to age, gender, ethnicity, education level as well as STI-related knowledge and systemic factors [ 10 ]. More recent research has explored more complex social and psychological factors such as perceived norms and perceived susceptibility informed by health psychology theories [ 11 – 13 ] and found these to be significant predictors of behaviour.…”
Section: Introductionmentioning
confidence: 99%